Measurements for pregnant drivers' comfort and safety - Serpil Acar; Alix M. Weekes (2006)
Pregnant women experience many different problems and difficulties with comfort and safety during car travel, which can be alleviated by accommodating pregnant women's anthropometry. There has been a dearth of information about pregnant anthropometry and subsequently women's needs have been neglected. This paper addresses the problem by presenting a detailed analysis of the anthropometric changes occurring throughout the body. The measurements have been selected for use in the vehicle design process, in order to best meet the needs of the automotive industry. The paper investigates the size and shape changes in pregnant women to calculate the possible exclusion rates for designs based on male and non-pregnant female data in order to help improving pregnant drivers' safety and comfort. The paper points out the importance of changes not only in the abdomen but also the chest and hip regions.